Effect of Water pH on Domestic Machine Washing Performance of Delicate Textiles - Nilüfer, Çakmakçı; Cevza, Candan; İlkiz, Arslan Başak (Walter de Gruyter GmbH, 2022)
Abstract In order to investigate the effect of washing water pH on textile damage for delicate garments, the study was conducted such that a customer survey was first applied to randomly selected users to analyze domestic washing machine using habits of Turkish consumers. Based on the findings of the survey, the experimental study was designed in two successive phases to investigate the dimensional and mechanical behavior of certain types of delicate textiles against varying washing conditions by taking in particular, water properties, namely pH, hardness, and temperature into account, and accordingly to determine the optimized washing conditions for such textiles. Firstly, tergotometer was employed as a washing machine simulator. Within the light of the results obtained, the experimental work of the second phase of the study was conducted, which involved a domestic washing machine as a real-life scenario. All of the results, including the correlation between the data sets obtained from the tergotometer and domestic washing machine trials, were statistically analyzed using Minitab 17. The study produced some important findings regarding the effect of washing water pH on delicate textiles, in addition to an algorithm for improving the present washing program, minimizing textile damage for mainly wool and silk garments.
Keywords: water ph; TP890-933; tergotometer; Textile bleaching, dyeing, printing, etc.; domestic washing machine